Change in attendance of stadiums in European leagues resulting from change in the number of clubs in cities: estimation with double difference method - K. A. Andreeva (Russian Journal of Economics and Law, 2017)
Objective: to assess the external effects of the emergence of a new football club in European cities.Methods: statistical methods, regression analysis, double difference method, generalization and typologization methods. Results: the article examines the problems of ensuring competition in the football market in the context of club matches attendance. The scientific researches are analyzed, which cover the issues of economic theories application to the problems in the sports sphere. It is concluded that a different economic approach is required in the countries with a low level of private capital in football, since the main power there belongs not to the clubs but to the regional governments.The article also introduces the concept of external effects for the football market. To assess their impact on competition in football, the analysis of all European football Championships since the early 1990s till today was carried out. Basis on the performed analysis, the types of the cities representatives in the highest football divisions are defined: super-competitive leagues, leagues with centripetal competition, leagues with distributed competition, and non-competitive leagues.Basing on the assessment of clubs configuration changes in different leagues, a number of hypotheses were formulated about the impact of configuration changes on the attendance of matches. The assessment is conducted by the method of double difference of the external effects of the clubs configuration changes in the cities of France, Italy, Hungary and Greece. Scientific novelty: the concept of external effect in the economics of football is applied to the assessment of attendance (the external effect of the change in the number of clubs in a city was formulated and evaluated), a typology of leagues according to the degree of competitiveness was introduced, based on the analysis of data for the period of twenty years. Practical significance: the basic results can be used for making decisions on the financial support for clubs from the lower divisions to enhance competition within the region for the attention of fans.